2018
DOI: 10.2147/ott.s164723
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and predictors of symptomatic venous thromboembolism associated with peripherally inserted central catheters in patients with nasopharyngeal carcinoma

Abstract: BackgroundDespite wide usage, peripherally inserted central catheter (PICC)-related venous thromboembolism (VTE) is common in nasopharyngeal carcinoma (NPC) patients.Patients and methodsThis was a retrospective cohort study of NPC patients with PICC insertions from February 2, 2007 to December 25, 2014 in Sun Yat-Sen University Cancer Centre. Univariable and multivariable logistic regression analyses were used to estimate odds ratios (ORs) with 95% confidence intervals (CIs) for the correlations between risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…General items include stage of carcinoma, thrombosis history, age, comorbidities, catheter insertion, chemotherapy, surgery and others [2224]. We previously have reported that VTE history, BMI, ECOG performance score and metastasis stage were significantly associated with symptomatic PICC-VTE in NPC patients [4]. In our study, the values of pre-treatment Plt and FDP were significantly higher in the VTE group.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…General items include stage of carcinoma, thrombosis history, age, comorbidities, catheter insertion, chemotherapy, surgery and others [2224]. We previously have reported that VTE history, BMI, ECOG performance score and metastasis stage were significantly associated with symptomatic PICC-VTE in NPC patients [4]. In our study, the values of pre-treatment Plt and FDP were significantly higher in the VTE group.…”
Section: Discussionsupporting
confidence: 48%
“…Furthermore, since intravenous infusion was administered for NPC patients for a long duration, they experience long term stay in bed or without active moving, which contributes to the formation of VTE. We previously reported that the incidence of PICC-VTE in NPC patients was 5.6% [4], and the figure tended to be even higher when asymptomatic thromboembolism was taken into consideration [5]. Although many cases of VTE are moderate and can be cured, it may cause recurrence, post-thrombotic syndrome or even pulmonary embolism [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…The ECOG score reflects the patient's activity status (Greipp et al., 1998 ). A higher ECOG score indicates poorer activity status (Liang et al., 2018 ). Previous studies found that lower patient activity was a risk factor of PICC‐RT (Yi et al., 2014 ; Yuxiu et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…3) compared to other solid tumours [102,103]. Researchers appoint to increased platelet aggregation and a blood hypercoagulable state in NPC patients, which might be key factors in triggering thrombosis [104][105][106]. However, in these patients, these mechanisms seem to be only relevant in the context of thrombosis related to the use of central catheters rather than thrombogenesis induced by the tumour biology itself [103,106].…”
Section: Reviewmentioning
confidence: 99%